Comparison between infrared and hot-blade beak trimming methods in white and brown pullets: performance, organ and bone development - Guarnieri, P. C.; Pagnussatt, H.; Aniecevski, E.; Dal Santo, A.; Leite, F.; Valentini, F. D. A.; Facchi, C. S.; Zaccaron, G.; Bosetti, G. E.; Rossatto, G.; Boiago, M. M.; Tavernari, F. C.; et al. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
The purpose of this study was to evaluate infrared beak trimming versus hot-blade beak trimming on performance, organ and bone development of laying pullets, using 240 birds, at 0-16 weeks of age, from two strains (white layer Hy-Line W36 and brown layer Hy-Line Brown). Infrared debeaking was performed on the first day of life in the hatchery, whereas hot-blade beak trimming was performed at eight days of age. Zootechnical performance at 6, 9, 12 and 15 weeks of age was analyzed. At the end of the trial, one Bird per experimental unit was euthanized for liver, gizzard, proventriculus, heart and small intestine relative weight evaluation. Both tibiotarsus were collected to measure bone breaking resistance, bone mineral content and bone densitometry. There was higher body weight and feed intake in both bird strains submitted to infrared beak trimming. Additionally, hot-blade white layers presented lower body development and feed intake. The debeaking methods did not influence relative organ weights or tibiotarsus parameters evaluated. We conclude that the infrared beak trimming method promotes better pullet body development than the conventional hot-blade method, improving feed intake, without compromising organ and bone development, being a more adequate debeaking method to be used in layer production.
Keywords: animal welfare; debeaking; densitometry; layer hens; poultry